2014
DOI: 10.5194/acp-14-12855-2014
|View full text |Cite
|
Sign up to set email alerts
|

The use of SMILES data to study ozone loss in the Arctic winter 2009/2010 and comparison with Odin/SMR data using assimilation techniques

Abstract: Abstract. The Superconducting Submillimeter-Wave LimbEmission Sounder (SMILES) on board the International Space Station observed ozone in the stratosphere with high precision from October 2009 to April 2010. Although SMILES measurements only cover latitudes from 38 • S to 65 • N, the combination of data assimilation methods and an isentropic advection model allows us to quantify the ozone depletion in the 2009/2010 Arctic polar winter by making use of the instability of the polar vortex in the northern hemisph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…1, an important O 3 loss in the lower stratosphere was also observed during other cold winters such as 2004/05 and 2007/08 (e.g. Singleton et al, 2007;Jin et al, 2006;Grooß and Müller, 2007;Jackson and Orsolini, 2008;Kuttippurath et al, 2009), which are also characterised by a ratio 1O Lower 3 /1O Middle 3 greater than 1 (Table 1).…”
Section: Overview Of Arctic Ozone Loss From 2002 To 2013mentioning
confidence: 54%
“…1, an important O 3 loss in the lower stratosphere was also observed during other cold winters such as 2004/05 and 2007/08 (e.g. Singleton et al, 2007;Jin et al, 2006;Grooß and Müller, 2007;Jackson and Orsolini, 2008;Kuttippurath et al, 2009), which are also characterised by a ratio 1O Lower 3 /1O Middle 3 greater than 1 (Table 1).…”
Section: Overview Of Arctic Ozone Loss From 2002 To 2013mentioning
confidence: 54%
“…The spatial and temporal gradients in these analyses are expected to reflect dynamical and chemical processes rather than the details of the observing system. This feature is exploited in several studies of the photochemistry of the middle atmosphere, especially in the polar regions (see Robichaud et al, 2010;Lahoz et al, 2011;Sagi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The comparison concluded that our estimation of the ozone loss is approximately 0.3 ppmv lower than other studies (Kuttippurath et al, 2010;Hommel et al, 2014;Wohltmann et al, 2013) . In Sagi et al (2014) 9 Atmos. Chem.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…Since PT in dry air is conservative under adiabatic conditions air parcels normally move on constant PT surfaces. However during polar night conditions considerable descent occurs within the polar vortex and because of the vertical gradients in ozone we must consider the effects of the vertical transport on the estimates of ozone loss.A first-order upstream scheme was implemented in the current version of the model in order to take account of the vertical 5 motion (Sagi et al, 2014). Since the general descent rate inside the vortex is approximately 1−2K per day it is slow enough for the effects of numerical diffusion to be negligible.…”
mentioning
confidence: 99%
See 1 more Smart Citation